Urgensi Teknologi Pendidikan Dalam Peningkatan Kualitas Pembelajaran Daring - Galantri Isra' Fania; Ria Nur Khasanah; Unik Hanifah Salsabila; Rahma Haifani Azizah; Anisa Listiyani (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
During the covid-19 pandemic as it is today, it has changed many sectors of human life, including the education sector. Many schools are reducing activities at school or even completely closing schools, only doing distance learning. Therefore, with distance learning, adequate technology and competent human resources are needed. This study aims to find out what educational technology is, how technology plays a role in education, what are the obstacles in implementing educational technology and how to use technology in schools, especially during the covid-19 pandemic. In this study, the author uses qualitative methods (library studies and interviews), in collecting data the author looks for several sources of reading that are in accordance with the topic of discussion, both from the internet, online journals and books. Then the author conducted an interview with one of the teachers at SDN Bojong through a virtual forum. From the results of the interview, it can be seen that the use of technology at SDN Bojong has not been effective, there are still many obstacles or obstacles in its implementation. However, educators continue to strive for the best in the use of technology so that they can help students in the learning process, so that students feel comfortable. In the learning process, SDN Bojong utilizes Google Classroom, Google Meet, Zom, Powerpoint and Youtube applications as learning media. And using Google Form and Quzziz as a medium for student evaluation.